2023
DOI: 10.3390/diagnostics13040619
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Benign Gallbladder Diseases Using Serum Surface-Enhanced Raman Spectroscopy Combined with Multivariate Statistical Analysis

Abstract: In this study, we looked at the viability of utilizing serum to differentiate between gallbladder (GB) stones and GB polyps using Surface-enhanced Raman spectroscopy (SERS), which has the potential to be a quick and accurate means of diagnosing benign GB diseases. Rapid and label-free SERS was used to conduct the tests on 148 serum samples, which included those from 51 patients with GB stones, 25 patients with GB polyps and 72 healthy persons. We used an Ag colloid as a Raman spectrum enhancement substrate. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…[96] It has been reported that increased levels of fibrinogen and platelets are related to GB malignancy. [97] Spectroscopy of bile samples using extracellular vesicles, near-infrared spectroscopy or voltage application has been used for the identification of GB carcinoma in cases of polypoid lesions [98][99][100][101][102] or GB stones and GB polyps. [103] It has been postulated that there is an association between overgrowth of small intestinal microbial flora detected by a hydrogen-methane simple breath test and GB polyps; this correlation is stronger in women.…”
Section: Diagnosismentioning
confidence: 99%
“…[96] It has been reported that increased levels of fibrinogen and platelets are related to GB malignancy. [97] Spectroscopy of bile samples using extracellular vesicles, near-infrared spectroscopy or voltage application has been used for the identification of GB carcinoma in cases of polypoid lesions [98][99][100][101][102] or GB stones and GB polyps. [103] It has been postulated that there is an association between overgrowth of small intestinal microbial flora detected by a hydrogen-methane simple breath test and GB polyps; this correlation is stronger in women.…”
Section: Diagnosismentioning
confidence: 99%